The Influence of Practice Exam Tutoring Services and E-Avis on Community Satisfaction in SIM Management at Banjarbaru Police Regency Mediated by Performance of Traffic Sat Members - Maulana Ansari; Musthafa, Musthafa (Sean Institute, 2023)
This study aims to analyze the effect of Tutoring Services for Practical Exams and E-Avis on Community Satisfaction in Management of SIMs at the Banjarbaru District Police, Mediated by the Performance of Members of the Traffic Unit. The population of this study is people who come to visit for the purposes of obtaining a driver's license. The research sample is 100 respondents, accidental sampling technique. Data collection uses a questionnaire. The data analysis tool uses Partial Least Quare, with SmartPLS 3.0 software. The results of the study are: 1) The practice exam tutoring service has a significant effect on member performance. 2) E-AVIS has no significant effect on member performance. 3) Practice exam tutoring services have a significant influence on community satisfaction. 4) E-AVIS has a significant influence on community satisfaction. 5) The performance of members of the Traffic Unit has a significant influence on community satisfaction. 6) The practice exam tutoring service has a significant influence on community satisfaction mediated by the performance of SatThen members. 7) E-AVIS is proven to have a significant influence on community satisfaction mediated by the performance of Traffic Unit members, in obtaining a driver's license at the Banjarbaru Police